Timing of Liver Imaging Result Release Is Associated with Patients with Cirrhosis Reviewing Results Prior to Providers - Louissaint, Jeremy; Deng, John; Tapper, Elliot B.; Turer, Robert W.; Hogan, Timothy P.; Yekkaluri, Sruthi; Dunn, Patrick; Singal, Amit G. (Applied Clinical Informatics, 2025)
Background Patients with cirrhosis are at high risk for developing hepatocellular carcinoma (HCC), warranting receipt of semiannual surveillance imaging with the potential to identify abnormal liver lesions. Since the implementation of the 21st Century Cures Act's Information Blocking provision, test results are immediately released to patients through the patient portal. There is an increasing trend of patients reviewing their results before their providers.Objective We aimed to determine whether the date and time characteristics of when the result is released to the electronic health record (EHR) are associated with patients reviewing results before providers.Methods In patients with cirrhosis undergoing ambulatory liver imaging, the date–time characteristics of when the result was released to providers in the EHR were categorized as outside regular work hours for holidays, weekends, or outside normal business hours. Logistic regression was used to determine the relationship between results released to the EHR outside work hours and whether the patient or provider was the first to review the result.Results We identified 850 imaging studies from 401 patients with a median age of 62 (interquartile range [IQR]: 53–69) years. Patient time to result review was shorter or equivalent to their providers for 57% of the results. A total of 170 (20.0%) of results were released outside regular work hours. There was an increased odds of the patient reviewing the result before providers for results released outside regular work hours (adjusted odds ratio [aOR] = 1.54, 95% CI: 1.08–2.20).Conclusion HCC screening results released to the EHR outside regular work hours is associated with patients reviewing these results before providers.
Keywords: patient–provider communication; 21st Century Cures Act; patient portal; hepatocellular carcinoma